BAKHTIYAR VAHABZADEH’S LYRICS - Perikhanim Soltangizi (Huseynova) (Research Focus International Scientific Journal, 2025)
The article states that the number of members of this school, which was founded in the 1950s and 1970s, is expected to increase in the future. A specific viewpoint is presented of the modern lyricism of Bakhtiyar Vahabzadeh. It is observed that in his recent works, Vahabzadeh, as in earlier decades, stays faithful to the fundamental internal direction of his poetry (with lyricism being a prominent direction and genre in his poetry). At the same time, it is justified that the lyrical beginning of these poems reflects new, important qualities in the poet’s work, with the idea of national independence being expressed in his lyricism with richer, more vivid colors. The author points out that the poet’s poems reflect not only his own "self" but also his character. The poem "I am dissatisfied with myself" is given as an example. I want reckoning From my nights and days. I am troubled, I am dissatisfied – With myself all my life. I am the broken-stringed instrument Of our artistic world, The only thing I am content with Is that I am dissatisfied with myself In this brief excerpt of poetry, the poet creates a reflection of his own character and conveys that he has been troubled throughout his life. Mehdi Huseyn rightly titled one of his articles about him "The Troubled Poet." The researcher shows that Bakhtiyar Vahabzadeh’s lyricism has developed in connection with the political, social, and global events of the era, and emphasizes that this has always been the case and continues to be so. This is why we see an entire era’s lyricism in his poetry, including his special lyricism, and in this sense, we can speak of various stages of his lyricism. For instance, it is possible to identify stages such as the 1950s–60s, the 1970s–80s, and national independence (the 1990s) in his lyricism. Of course, it would not be correct to think that these stages in Bakhtiyar Vahabzadeh’s poetry are sharply distinct from one another. Vahabzadeh’s lyricism has maintained its individual poetic spirit and characteristics throughout all stages of its development. Subsequently, the researcher discusses the development, deepening, and enrichment of the idea-philosophical and poetic content of Bakhtiyar Vahabzadeh’s lyricism, as well as the adoption of new modern qualities. In this regard, the researcher characterizes the poet’s recent works, coinciding with the late 20th century, as a continuation of his poetic school. The author notes that the poet reflects on issues of national independence and sovereignty in his poems, directing poetic tools towards clarifying, meaningful and, most importantly, concrete solutions to these issues. The researcher states that the poet’s lyrical "self" expresses itself in relation to these matters. The researcher reviews the poet’s recent lyricism as a cohesive whole, first noting the multifaceted nature of the national independence theme in Vahabzadeh’s poetry. The idea of national independence attracts attention in Vahabzadeh’s work, with aspects such as self-awareness, oppression and freedom, our national identity, Turkism, the contemporary state of the nation, human acknowledgment before God, and so on. The researcher concludes that the poet’s "self" is entirely engaged in explaining and understanding these concepts for himself. The researcher enters into scientific debate, basing his reflections on quotations. The article examines the themes of love in Bakhtiyar Vahabzadeh’s lyricism. In poems such as “May the nights extend”, “Which of us is absent”, “Was not worth a greeting”, “What a pity”, “Drizzling rain”, “You said”, “Just me and silence”, “I would like to forget”, “You should know” and others, the elements of love are explored, with a focus on reunion, longing, separation, and the feelings and thoughts of the lover. The researcher characterizes the poet’s lyrical hero as a purveyor of feelings and emotions, a bearer of universal values, and a figure with unique characteristics. Philosophical ideas in the poet’s love poems are also highlighted. The researcher provides scientific substantiation of their opinions through quotations and engages in extensive debate. The article emphasizes the search for trust, loyalty, and belief among loving hearts in the poet’s creative work. The researcher also characterizes the poet as one who describes the realm of the heart. The researcher points out that in the quatrain of “I said-you said”, the poet creates a philosophical meaning in just four lines, shedding light on the poem’s merits. By bringing attention to the poet’s definition of love, the researcher recalls the sayings of classical poets. This involves referencing the works and love philosophy of Fuzuli and Khagani, comparing Bakhtiyar Vahabzadeh’s philosophy of love with that of the classical poets. The article also discusses the poet’s love for his homeland and language. Bakhtiyar Vahabzadeh is studied as a lover of his homeland and language. The author highlights that the theme of love holds a special place in the poet’s more than seventy books of poetry. By reviewing the creation dates of the poems “Was not worth a greeting” and “What a pity” the author compares their ideas, content, and artistic aspects. The author also draws attention to the opinions of well-known and influential thinkers about the poet.